URINALYSIS AS A PREDICTOR FOR URINARY TRACT INFECTION: AN OBSERVATIONAL STUDY - K, Swetha; B, Sravanthi; M, Sridhar; Urooj, Aqsa; K, Ratnamala (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The aims and objectives of the study are to find the usefulness of urine dipstick and urinalysis in children with an intention to identify the parameters which most likely point toward the presence of urinary tract infection (UTI), whether a combination of the parameters analyzed rather than single parameter is useful in suggesting the presence or absence of UTI. Methods: The study was a prospective observational study done in 401 children below 16 years of age with clinically suspected UTI. Results: The sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) of dipstick leukocyte esterase (LE) and nitrite were 85%, 93.1%, 75.6%, 96.1% and 51.2%, 99.1%, 93.2%, 89.1%, respectively. In urine microscopic analysis, the sensitivity, specificity, PPV, NPV of bacteria were 68.5%, 96.9%, 84.6%, and 92.6% and those of pus cells were 80%, 93.1%, 74.4%, and 94.9%. Conclusion: Combination of parameters, i.e., LE, nitrite, and bacteria or LE, nitrite, and pus cells are good screening tools to predict and rule out UTI. Of the individual parameters analyzed, negative nitrites in dipstick and absence of bacteria in urine microscopy almost rule out UTI caused by most uropathogens.